THEORETICAL APPROACHES TO ASSESSING THE EFFICIENCY OF FOREIGN INVESTMENTS - Rozali Ashiraliev (Ecominds Press, 2025)
This article systematically analyzes theoretical approaches, assessment methods and international methodologies for assessing the efficiency of foreign investments. In particular, the assessment mechanisms developed by leading organizations such as UNIDO, the World Bank, Little-Mirrless, Cost-Benefit Analysis, Ernst & Young are studied on a comparative basis. The author substantiates with theoretical arguments that foreign investments are not only a financial flow, but also a major source of technological transfer, innovation, market relations and modern management experience. The contribution of foreign investments to economic development is revealed within the framework of theories of international investment integration, risk-return model and investment portfolio approaches. At the same time, institutional and infrastructural recommendations aimed at increasing the efficiency of foreign investments are presented on the example of Uzbekistan. The results of the study allow using them as a theoretical and practical resource for assessing foreign investments and their more targeted management.
Keywords: Foreign investments, investment efficiency, UNIDO method, World Bank methodology, investment risk, diversification, risk-return model, international investment integration, cost-benefit analysis, investment portfolio, investment environment of Uzbekistan.